LEGENDARY TEXT MALIN KUNDANG AS MEDIA MORAL VALUE FOR STUDENT THROUGH INTERNET - Jetro Limbong; Wikanengsih Wikanengsih (IKIP Siliwangi, 2021)
This research explain how using legend text Malin Kundang through internet in learning. Research uses descriptive qualitative with sample is seven grade Junior High School who take Indonesian language lessons. Collection by observation and test methods. Instruments used were observation sheets and questions in form. Research validation was tested with external validity. Data analyzed using test of knowledge student about moral value in Malin Kundang text. Results of study are (1) Effective use of Malin Kundang legend text as a medium for moral values. (2) Internet as a stimulus to help student for knowing moral value. 3) Students get values in Malin Kundang text. Teacher excepted to use internet include value moral in text learning content.